(untitled) (Comillas Journal of International Relations, 2024)
As an organization committed to working with and standing alongside those who have been forcibly displaced from their homes, advocacy is a core element of Jesuit Refugee Service’s work around the world. With policymakers, donor governments, and host communities, JRS advocates for, and with, those who seek safety and the opportunity to rebuild a life for themselves and their families. Through a network of staff across the globe implementing programs each and every day, JRS identifies the challenges faced in meeting the basic needs of those we serve, and which policies can improve those circumstances. In this article, we share examples of three areas where JRS has exerted influence and action on such policies. This includes access to refugee education, protecting the right to asylum, and placing a spotlight on one of the world’s most forgotten crises, the conflict in Syria.